2012
DOI: 10.1242/jcs.095422
|View full text |Cite
|
Sign up to set email alerts
|

E-cadherin inhibits nuclear accumulation of Nrf2: implications for chemoresistance of cancer cells

Abstract: SummaryNrf2 has an anti-carcinogenic effect. However, an increase in Nrf2 activity is also implicated in cancer chemoresistance. A switch from E-cadherin to N-cadherin affects the transdifferentiation and metastasis of cancer cells. In view of the key role of this switch in cancer malignancy, we investigated the regulatory effect of E-cadherin on Nrf2. In HEK293 cells, overexpression of E-cadherin inhibited the nuclear accumulation of Nrf2, and prevented Nrf2-dependent gene induction. GST pull-down and immunoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 41 publications
3
51
0
Order By: Relevance
“…In line with this concept is also the recent finding that oxidative stress is causing disruption of adherens junctions as a consequence of loss of proteinprotein interactions between b-catenin and E-cadherin [52,68]. In addition, Nrf2, a regulator of anti-oxidant gene expression, might be recruited to E-cadherin thereby inactivating Nrf2 and favoring oxidative stress and carcinogenesis [69]. Nrf2 has been linked to the expression of heme oxygenase-1, the key control enzyme of heme degradation generating end products that act as anti-oxidants [70].…”
Section: Discussionmentioning
confidence: 74%
“…In line with this concept is also the recent finding that oxidative stress is causing disruption of adherens junctions as a consequence of loss of proteinprotein interactions between b-catenin and E-cadherin [52,68]. In addition, Nrf2, a regulator of anti-oxidant gene expression, might be recruited to E-cadherin thereby inactivating Nrf2 and favoring oxidative stress and carcinogenesis [69]. Nrf2 has been linked to the expression of heme oxygenase-1, the key control enzyme of heme degradation generating end products that act as anti-oxidants [70].…”
Section: Discussionmentioning
confidence: 74%
“…5b and Additional file 1: Figure S4B). It has been reported that Nrf2 activation could promote cancer metastasis by modulating epithelial-mesenchymal transition (EMT) [24]. Nrf2 knocked-down in cancer cells before TEM CM stimulation was performed to illustrate the relationship between TEM-induced cancer cell Nrf2 activation and EMT (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of E-cadherin results in inhibition of Nrf2 nuclear translocation (39). We therefore evaluated E-cadherin levels in an attempt to explain the inability of CysLTr1 2/2 mice to translocate Nrf2.…”
Section: Cyslts Induce Nrf2 Nuclear Translocation Through Indirect Mementioning
confidence: 99%